(untitled) (Fourth World Journal, 2025)
This literature review casts a rather large net aimed at identifying and assembling the different veins of research that primarily im- pact indigenous health promotion and interventions, and secondarily, immigrant health and interventions. It is especially concerned with specimens of participatory research, community based participatory research (CBPR), and community-generated media. A large scope of the related data currently available is qualitative and/or quasi-experimental at best. There are a number of operational constraints that contribute to this, and the act of conducting research in these populations is stymied by some of the same factors that are foundational to many of the salient health issues that emerge. Sociocultural isolation and invisibility to mainstream society; a seasoned distrust of outsiders, government officials, and academic researchers; and a general state of marginalization and political disenfranchisement all compound in establishing similar barriers to positive health outcomes and high quality research designs and impact evaluation. This paper will explore a non-indexed list of important themes that emerge through the intersection of indigenous health: community health, participatory research, community and indigenous media, limited quantitative data, and the development of culturally specific instruments or programs.